Healing plasma current ramp-up by nitrogen seeding in the full tungsten environment of WEST. (1st April 2022) - Maget, P; Manas, P; Artaud, J-F; Bourdelle, C; Bucalossi, J; Bufferand, H; Ciraolo, G; Desgranges, C; Devynck, P; Dumont, R; Fedorczak, N; Felici, F; et al.
Abstract: Achieving a successful plasma current ramp-up in a full tungsten tokamak can be challenging due to the large core radiation (and resulting low core temperature) that can be faced with this heavy metallic impurity if its relative concentration is too high. Nitrogen injection during the plasma current ramp-up of WEST discharges greatly improves the core temperature and magnetohydrodynamic (MHD) stability. Experimental measurements and integrated simulations with the RAPTOR code, complemented with the QuaLiKiz neural network for computing turbulent transport, allow a detailed understanding of the mechanisms at play. Increased edge radiation during this transient phase is shown to improve confinement properties, driving higher core temperature and better MHD stability. This also leads to increased operation margins with respect to tungsten contamination.